Meningkatkan Aktivitas Dan Hasil Belajar Biologi Pada Materi Metabolisme Melalui Penggunaan Media Pembelajaran Power Point - Nurazimar Nurazimar (Madaris: Jurnal Guru Inovatif, 2022)
Metabolism is one of the biology subject matter that is considered difficult by students, it can be seen from the low grades of students in the KD. This is because metabolism is an abstract material so we need the right media to help deliver the subject matter so that it is more concrete and easy to understand. The purpose of this study was to increase the activity and learning outcomes of biology through the use of power point learning media in class XII IPA MAN 4 Pasaman Barat. This action research method is carried out through the stages of planning, implementation, observation and reflection. This action research was carried out in 2 cycles with 4 meetings. Data collection techniques using observation instruments and test scores for learning outcomes. The results showed that the use of power point learning media can improve student learning outcomes. This can be seen in the achievement of the first cycle which achieved completeness as many as 17 of 21 students with a percentage increase of 76% with an average value of 76.42 learning outcomes and an increase in the second cycle with 100% completeness with an average value of 85.92. It can be concluded that using power point learning media can increase student activity and learning outcomes on metabolic material in class XII IPA MAN 4 Pasaman Barat.